Capturing Structural Variants of Herpes Simplex Virus Genome in Full Length by Oxford Nanopore Sequencing - Rajagopalan Saranathan; Emmanuel Asare; Lawrence Leung; Anna Paula de Oliveira; Katherine E. Kaugars; Claire V. Mulholland; Regy Lukose; Michael Berney; William R. Jacobs (Microbiology Spectrum, 2022)
ABSTRACT Genome sequencing and assembly of viral genomes within the Herpesviridae family, particularly herpes simplex virus (HSV), have been challenging due to the large size (~154 Kb), high GC content (68%), and nucleotide variations arising during replication. Oxford Nanopore Technology (ONT) has been successful in obtaining read lengths ranging from 100 Kb up to 2.3 Mb. We have optimized DNA extraction and sequencing with ONT to capture the whole genome of HSV-1 as a single read. Although previous studies described the presence of four different genome isomers of HSV, we provided the first report on capturing all four variants’ full-length genome as single reads. These isomers were found to be present in almost equal proportion in the sequenced DNA preparation. IMPORTANCE With the advent of next-generation sequencing platforms, genome sequencing of viruses can be performed in a relatively shorter time frame in even the most austere conditions. Ultralong read sequencing platforms, such as Oxford Nanopore Technology (ONT), have made it possible to capture the full-length genome of DNA viruses as a single read. By optimizing ONT for this purpose, we captured the genome (~154 Kb) of a clinical strain of herpes simplex virus 1 (HSV-1). Additionally, we captured full-length sequences of the four isomers of lab-grown HSV-1 virus and were able to determine the frequency of each within the isogenic population. This method will open new directions in studying the significance of these isomers and their clinical relevance to HSV-1 infections. It will also improve basic studies on the recombination and replication of this virus.